Comparative assessment of the indices of the left ventricle post-infarction remodelling of the left ventricle and its dependence on the strategy of acute myocardial infarction management - D. M. Zhidovich; L. V. Shcheglova (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Comparative assessment of the indices of post-infarction remodelling of the left ventricle was carried out in the patients with myocardium reperfusion (thrombolytic therapy) and without reperfusion. ECG was performed for all patients on admission to the hospital and then 3 and 6 months later. The results obtained demonstrated that after the acute period of myocardial infarction there was no difference between the parameters under control. At the same time the results of dynamic monitoring confirmed that later on the patients felt some peculiarities during the left ventricle remodelling process. Three months later there was an increase of the left ventricle sphericity index during the systoly in the patients of group II. Six months later the patients of group II showed significant difference in five indices of remodelling versus the patients on thrombolitic therapy.